Training courses on Expert Knowledge Elicitation. Issue 9 (30th September 2020) - Colson, Abigail; Bolger, Fergus; French, Simon; Frewer, Lynn; Gosling, John Paul; Hart, Andy; Quigley, John; Rowe, Gene
Abstract : This final report summarises the objectives, activities and delivery, evaluation, and any future recommendations for each of the four trainings delivered under this contract. Sections are organised in chronological order consistent with the order in which trainings were delivered: Section 3 details the Sheffield course, Section 4 Semi‐formal, Section 5 Delphi, and Section 6 Cooke. Section 7 provides overarching conclusions from across all trainings.